2018
DOI: 10.1371/journal.ppat.1007220
|View full text |Cite
|
Sign up to set email alerts
|

The Sec1/Munc18 (SM) protein Vps45 is involved in iron uptake, mitochondrial function and virulence in the pathogenic fungus Cryptococcus neoformans

Abstract: The battle for iron between invading microorganisms and mammalian hosts is a pivotal determinant of the outcome of infection. The pathogenic fungus, Cryptococcus neoformans, employs multiple mechanisms to compete for iron during cryptococcosis, a disease primarily of immunocompromised hosts. In this study, we examined the role of endocytic trafficking in iron uptake by characterizing a mutant defective in the Sec1/Munc18 (SM) protein Vps45. This protein is known to regulate the machinery for vesicle traffickin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 59 publications
1
27
1
Order By: Relevance
“…Our study adds to a growing body of evidence linking mitochondrial function to virulence in C. neoformans and the related Cryptococcus gattii species complex (37,(41)(42)(43)(44)(45)(46). It is known, for example, that the variation in both intracellular proliferation rate within phagocytic cells and virulence among some genotypes of the C. gattii species complex can be attributed to differences in mitochondrial morphology (47,48).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Our study adds to a growing body of evidence linking mitochondrial function to virulence in C. neoformans and the related Cryptococcus gattii species complex (37,(41)(42)(43)(44)(45)(46). It is known, for example, that the variation in both intracellular proliferation rate within phagocytic cells and virulence among some genotypes of the C. gattii species complex can be attributed to differences in mitochondrial morphology (47,48).…”
Section: Discussionmentioning
confidence: 72%
“…It is known, for example, that the variation in both intracellular proliferation rate within phagocytic cells and virulence among some genotypes of the C. gattii species complex can be attributed to differences in mitochondrial morphology (47,48). Genetic studies also identified mitochondrial proteins with diverse functions that influence virulence in C. neoformans, and these proteins include Lys4 (amino acid biosynthesis), Vps45 (intracellular trafficking), Atm1 (mitochondrial iron uptake), Fzo1 (mitochondrial fusion), and Sod2 (superoxide dismutase) (41)(42)(43)(44)(45). Components of the ETC are also important for virulence as demonstrated by the reduced virulence of a mutant lacking alternative oxidase (46).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial function is important for cryptococcal virulence ( 24 , 25 ), but we wondered whether and how mitochondrial morphology influences cryptococcal pathogenesis. To probe this relationship between form and function, we deleted genes that encode the major actors in the normal maintenance of mitochondrial morphology.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies in C. neoformans revealed important roles in heme use for endocytosis and endomembrane trafficking machinery, including the ESCRT proteins Vps22, Vps23, and Snf7, and proteins for clathrin-mediated endocytosis such as Chc1 (clathrin heavy chain 1), Las17 (a nucleation‐promoting factor for actin assembly), and Rvs161/Rvs167 (vesicle scission proteins; amphiphysins) ( 25 , 26 , 28 ). A recent study also highlighted a role for the SNARE regulator Vps45 in iron use from heme ( 34 ). Furthermore, a hemophore encoded by CIG1 is unique to C. neoformans and is involved in heme use and virulence ( 35 ).…”
Section: Introductionmentioning
confidence: 99%